The Campotosto Seismic Gap in Between the 2009 and 2016–2017 Seismic Sequences of Central Italy and the Role of Inherited Lithospheric Faults in Regional Seismotectonic Settings. Issue 8 (9th August 2018) - Falcucci, E.; Gori, S.; Bignami, C.; Pietrantonio, G.; Melini, D.; Moro, M.; Saroli, M.; Galadini, F.
Abstract: The 2016–2017 seismic sequence, in central Italy, was caused by the Mt. Vettore‐Mt. Bove active fault system, which generated three mainshocks, the largest one of Mw 6.6, on 30 October 2016. On 18 January 2017, four Mw 5–5.5 seismic events nucleated on the Campotosto active fault. The fault is considered as potentially responsible for M ~6.6 seismic events and a seismic gap. The structure also nucleated a Mw 5.4 aftershock during the 2009 L'Aquila seismic sequence. We here combined new geological/geomorphological field data, 1945 aerial photographs interpretation, geodetic (Differential Interferometric Synthetic Aperture Radar and Global Positioning System) data, and local historical seismicity analysis to determine how much of the Campotosto seismogenic source ruptured during the 2009 and 2016–2017 seismic sequences. The obtained residual seismic moment of the Campotosto seismic gap is in the range Mw 6.4–6.6 earthquake. Moreover, the review of the regional tectonic setting and evolution allowed us a brand new and comprehensive reading of the seismotectonics for the region, in terms of both seismic potential and segmentation of the seismogenic sources, which results strictly connected to the long‐term activity of inherited lithospheric discontinuities, among which the major Ancona‐Anzio fault. We here first highlight that such regional structures strongly influenced the structural setting and evolution of the surrounding regions, in a progressive and continuous process of tectonic inversions, which implies that structural heritage must be understood and considered when dealing with seismotectonics of a given tectonically active region. Key Points: Geological/geomorphological information is coupled with seismological and geodetic data related to the 2009 and 2016–2017 central Italy seismic sequences Coseismic dislocation model, based on GPS and InSAR data related to the 18 January 2017 earthquakes on the Campotosto fault, is presented The residual seismogenic potential of the Campotosto fault is on the order of 6.4–6.5 moment magnitude earthquake